Case report: Neuroacanthocytosis associated with novel variants in the VPS13A gene with concomitant nucleotide expansion for CANVAS and assessment with osmotic gradient ektacytometry - Paucar, Martin; Wincent, Josephine; Rubin, Charlotta; Peikert, Kevin; Kyhle, Josefin; Hertegård, Stellan; Möller, Riita; Beshara, Soheir; Svenningsson, Per (Frontiers in Neuroscience, 2024)
Background and objectivesThe diseases historically known as neuroacanthocytosis (NA) conditions include VPS13A disease (formerly chorea-acanthocytosis) and XK disease (formerly McLeod syndrome). Here we report a patient with a hyperkinetic syndrome associated with variants in VPS13A with a concomitant homozygous nucleotide expansion in Replication factor C, subunit 1 (RFC1) and evaluate the role of ektacytometry for the assessment of acanthocytes.MethodsInvestigations included clinical assessments, neuroimaging studies, laboratory analyses, blood smears, ektacytometry, psychometric evaluation, and genetic analyses. Using ektacytometry, an osmoscan curve is obtained yielding a diffraction pattern as a measure of average erythrocyte deformability from circular at rest to elliptical at a high shear stress. The pattern allows the derivation of several parameters (mainly EI-max, O-min and O-Hyper points). Samples from two other patients with genetically proven VPS13A disorder and XK disease and varying numbers of acanthocytes as well as from a fourth with acanthocytosis due to liver failure were also analyzed.Case presentationThe patient has impulsivity, chorea and disabling feeding dystonia refractory to treatment and 15% acanthocytes in peripheral blood. Genetic workup revealed compound heterozygous variants c.1732_1733del; p.(V578Ffs*9) and c.8282C > A, p.(S2761*) in VPS13A with absence of chorein in the blood, the latter variant is novel. In addition, he harbors a homozygous nucleotide expansion in the RFC1 gene, reported in cerebellar ataxia, neuropathy, vestibular areflexia syndrome (CANVAS). However, the patient does not display ataxia yet. Ektacytometry revealed significantly reduced erythrocyte deformability in this patient and in another man with VPS13A disease. In contrast, the patient with XK disease had 2% acanthocytes and mild abnormalities on ektacytometry. In the three cases, ektacytometry yielded a specific pattern, different from acanthocytosis due to liver failure.ConclusionPathogenicity of the VPS13A variants is confirmed by absence of chorein, long-term follow up is required to evaluate any synergistic impact of for the underlying CANVAS mutation. New generation ektacytometry provides an objective measurement of erythrocytes’ rheological properties and may serve as a complement to blood smears. Finally, ektacytometry’s ability to detect deformability of erythrocytes in NA seems to depend on the degree of acanthocytosis.